Study of an optimal surface property of carbide cutting tool by surface modification method - Razali, Mohd Nizar Mhd; Hamedon, Zamzuri B.; Yusoff, A. R.; Ahmad, Syarifah Nur Aqida Syed; Redza, A.; Jamaludin, Ahmad Shahir (2019)
This thesis introduces the effect of textures on carbide insert rake surface to the surface roughness on using laser surface texturing. Surface texturing is one of the techniques for enhancing tribological properties of mechanical components. This is also widely used which contributes a lot in numerous engineering applications. Various parameters of pattern have been used to improve tribological performance. Parallel grooves has been used because able to trap wear debris, change stress distribution and low surface roughness. The fabrication of textures on carbide insert surface is one of the predominant methods to enhance the sustainability of laser process with cemented carbide insert. Laser process was utilized using CK-FB3D 3-Axis Control fiber laser marker to fabricate textures that were effective use to cut the tool. Olympus BX51M metallurgical microscope was using to check condition of the rake surface carbide insert. After that, depth of cut of the laser on the carbide insert was investigate using video measuring system. Furthermore, the surface roughness was utilized using surface roughness tester. Carbide insert has been tested using four parameters and found that relatively low scanning speed and frequency resulted in less surface roughness for textured carbide insert. Low surface roughness was discovered because high hardness of the carbide insert would make the less friction when cutting the tool.